Sistem Pendukung Keputusan Penilaian Kinerja Tenaga Kependidikan (TENDIK) Dengan Menggunakan Metode SMARTER - Utomo, Dito Putro; Purba, Bister (Jurnal Komtika (Komputasi dan Informatika), 2021)
The success of a university is not only seen from the role of Educators (Lecturers) but also the role of Education Personnel (TENDIK). Educational Personnel (TENDIK) includes Administrative Personnel in universities. Work performance is the main factor of the success of higher education performance. The results of good work given will have a good impact on universities. TENDIK who excels are also competent in higher education and contributes to the joint progress of both TENDIK and universities. Apart from lecturers, TENDIK is also an asset owned by universities. Rewards or awards given to TENDIK can be done by assessing the performance results of each TENDIK. The reward given to TENDIK is a form of appreciation for the performance carried out at the university. Giving rewards to TENDIK must be based on a proper and accurate performance assessment. The problem is that there is no definite reference used to evaluate the performance of TENDIK in giving rewards. The performance assessment carried out must be objective, of course, with an objective assessment the results obtained from the TENDIK performance assessment will not be a problem for other TENDIK. Decision Support System is a computer-based information system that is used to assist in decision making by utilizing certain data and models to support a solution in solving a semi-structured and non-structured problem. SMARTER is one of the methods in the Decision Support System that provides recommendations to decision makers based on relevant criteria, which in determining the criteria and sub-criteria and their weight values ​​use ROC (Rank Order Centroid). Of the several criteria used for the selection process using the alternative SMARTER method with the name A4 with a final utility value of 64.25%